Trend of Gross Domestic Product and Per Capita Income of Bangladesh: Past, Present, and Future - Vasagan, V. T. (Talaa : Journal of Islamic Finance, 2022)
Bangladesh's per capita income was half of that of India in 2007. Today, it has surpassed India. The Asian Development Bank has estimated that Bangladesh's GDP will grow at a rate of 6.6% hereafter. According to the 2022 Economic Freedom Index, Bangladesh's economy placed in the 137th position with a score of 52.7 in the World. In the Asia-Pacific region, Bangladesh ranked 29th position out of 39 countries. The resilience of COVID-19 impinged the average growth of the economy. International Monetary Fund (IMF) has envisaged that the World may experience a challenging recession-like situation in 2023. Hence, the present paper attempts to predict the economic condition of Bangladesh through its GDP and Per Capita Income. The study considers 51 years of GDP and Per Capita Income growth data. It has adapted the Trend Projection Method, a linear regression technique, and the Least Square method to analyze data to get the future trend. It has been found that GDP was grown at an average rate of 4.4% and Per capita income at an average rate of 1.8% since 1971. The study reveals that GDP and Per Capita Income may grow at 7% and above hereafter. Hence, appropriate strategies and economic policies of the Government of Bangladesh create a defendable position that safeguards the country's economic condition.